2006
DOI: 10.1364/ol.31.000059
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic tuning of photonic crystal circuits

Abstract: By integrating soft-lithography-based nanofluidics with silicon nanophotonics, we demonstrate dynamic, liquid-based addressing and high ⌬n / n͑ϳ0.1͒ refractive index modulation of individual features within photonic structures at subwavelength length scales. We show ultracompact tunable spectral filtering through nanofluidic targeting of a single row of holes within a planar photonic crystal. We accomplished this with an optofluidic integration architecture comprising a nanophotonic layer, a nanofluidic delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
121
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(121 citation statements)
references
References 10 publications
0
121
0
Order By: Relevance
“…Such a structure can be used as a sensor, whose principle of operation is based on the cut-o wavelength shift caused by the in ltration of the holes. In ltration can be performed by various selective in ltration techniques, which have been experimentally demonstrated, such as using an integrated micro uidic circuit [24], an actuated microtip [25] or micropipette [26] with a high precision and good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Such a structure can be used as a sensor, whose principle of operation is based on the cut-o wavelength shift caused by the in ltration of the holes. In ltration can be performed by various selective in ltration techniques, which have been experimentally demonstrated, such as using an integrated micro uidic circuit [24], an actuated microtip [25] or micropipette [26] with a high precision and good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups used evanescent coupling from ridge waveguides ͑WGs͒ to a silicon PhC nanocavity in a serial geometry, achieving sensitivities of ⌬n / n = 0.002. 9,10 Sensors based on measuring the transmission properties of PhC-WGs were investigated by Erickson et al 11 and Skivesen et al 12 Cunningham et al 13 utilized an alternative approach based on detecting the RI from a two-dimensional Bragg grating. However, as for SPR and interferometric methods this approach is nonlocal and requires a large analyte volume.…”
mentioning
confidence: 99%
“…8 However, the nanometer-scale precision required to realize sophisticated and optimized geometries eventually becomes a limiting factor in achieving high-Q cavities, as pointed out by Asano et al 9 Recently, several groups have reported demonstrations of postprocessed PCS structures, granting them the flexibility to tune or reconfigure device properties to suit various applications at any time after the PCS is fabricated. [10][11][12][13] In particular, Intonti et al introduced a "pixel by pixel" approach for writing and rewriting PCS defect structures via fluid infiltration. 12 Theoretical results of Tomljenovic-Hanic et al showed that high Q-factor cavities could be achieved in PCSs from fluid infiltration 14 by forming doubleheterostructured geometries, providing an integrated optofluidic sensing architecture.…”
mentioning
confidence: 99%